A CORPUS DRIVEN COMPARISON OF ENGLISH AND UZBEK LITERARY PROSE - Satibaldieva Nigora (Modern American Journals, 2025)
This article analyses the dynamics of lexical change in English and Uzbek literary language between the nineteenth and twentieth centuries. Drawing on a 7-million-word diachronic subset of the Corpus of Historical American English and a newly compiled 3-million-word Uzbek Fiction Corpus, we trace the emergence, decline, and semantic drift of high-frequency lemmas. Statistical measures – log-likelihood, keyness, and adjusted type–token ratio – reveal parallel patterns of technological expansion and the attrition of archaic lexis, but also divergent trajectories shaped by colonial contact, script reform, and nation-building. The findings refine existing models of lexico-semantic evolution and offer practical implications for historical lexicography and literary translation.
Keywords: Lexical change, diachronic corpus, English literature, Uzbek literature, nineteenth century, twentieth century, keyness analysis, historical lexicography